The STR polymorphism (AAAAT)n within the intron 1 of the tumor protein 53 (TP53) locus in 17 populations of different ethnic groups of Africa, America, Asia and Europe - Azofeifa, Jorge (2004)
The STR (AAAAT)n within intron 1 of the TP53 locus was screened in 17 populations from 3 main ethnic groups: Europeans, Asiatics, and Africans, and from the hybrid population of Costa Rica (1968 samples). Three alleles, 126/7 (bp/copies of the repeat), 131/8 and 136/9 were the most prevalent in all populations. Other alleles rarely reached frequencies of 10% or higher. Observed heterozygosities ranged between 0.351 and 0.829. Patterns of diversity fit well with both the geographic origin of the samples and the history of the populations screened. A statistical test suggests that single-step mutational events have been the main mechanism producing new alleles at this locus. Fixation indexes (RST) for this marker showed an effect of population subdivision on divergence only within the Asiatic group; they were insensitive at the level of major ethnic groups as well as within Africans and within Europeans.